2018
DOI: 10.1055/s-0043-122494
|View full text |Cite
|
Sign up to set email alerts
|

Risk of colonic diverticular rebleeding according to endoscopic appearance

Abstract: Background and study aims  Re-commencement of bleeding (rebleeding) of colonic diverticula after endoscopic hemostasis is a clinical problem. This study aimed to examine whether endoscopic visibility of colonic diverticular bleeding affects the risk of rebleeding after endoscopic hemostasis. Patients and methods  We performed a retrospective review of endoscopic images and medical charts of patients with colonic diverticular bleeding who underwent endoscopic hemostasis. Endoscopic visibility was classified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Blood flow is bidirectional in these arteries. When endoscopists only treat on top of the stigmata or remotely from it, arterial blood flow often continues and rebleeding through the side hole of the artery (underneath the stigmata) is likely [10, 11].…”
Section: Diverticular Vascular Anatomymentioning
confidence: 99%
See 2 more Smart Citations
“…Blood flow is bidirectional in these arteries. When endoscopists only treat on top of the stigmata or remotely from it, arterial blood flow often continues and rebleeding through the side hole of the artery (underneath the stigmata) is likely [10, 11].…”
Section: Diverticular Vascular Anatomymentioning
confidence: 99%
“…This is critical for success of endoscopic hemostasis particularly if bleeding is from the base, where the artery is larger. If the endoscopist attempts to close the diverticular neck with hemoclips when the stigmata is in the base, rebleeding is very common [10, 11]. Based on arterial vascular anatomy (Fig.…”
Section: Limitations Problems and Risk Factors For Rebleedingmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Diverticular bleeds are the most common cause of lower GI bleeding, and reports have shown that up to 75% of cases spontaneously resolve. 43,44 Yet, the remaining cases have a high rate of rebleeding after initial endoscopic hemostasis (11%-47%). 43,45 On top of this, the incidence of diverticular bleeds is rising as more patients are on antithrombotic therapy.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…43,44 Yet, the remaining cases have a high rate of rebleeding after initial endoscopic hemostasis (11%-47%). 43,45 On top of this, the incidence of diverticular bleeds is rising as more patients are on antithrombotic therapy. 37 Hence, effective endoscopic modalities are critical to avoid recurrent bleeding, surgery, reduce costs and prolonged hospital stays.…”
Section: Clinical Applicationmentioning
confidence: 99%